Computational analysis of the optical response of ZnSe with d-orbital defects. (18th May 2022) - Pike, Nicholas A; Pachter, Ruth; Martinez, Alan D; Cook, Gary
Abstract: The doping of wide band-gap semiconducting ZnSe by transition metal (TM) atoms finds applications from mid-infrared lasing, sensing, photoelectrochemical cells, to nonlinear optics. Yet understanding the response of these materials at the atomic and electronic level is lacking, particularly in comparing a range of TM dopants, which were studied primarily by phenomenological crystal-field theory. In this work, to investigate bulk ZnSe singly doped with first-row TM atoms, specifically Ti through Cu, we applied a first-principles approach and crystal-field theory to explain the origin of the infrared absorption. We show that the use of an appropriate exchange–correlation functional and a Hubbard U correction to account for electron correlation improved the determination of the electronic transitions in these systems. We outline an approach for the calculation of the crystal-field splitting from first-principles and find it useful in providing a measure of dopant effects, also in qualitative comparison to our experimental characterization for ZnSe doped with Fe, Cr, and Ni. Our calculated absorption spectra indicate absorption signatures in the mid-infrared range, while the absorption in the visible portion of the spectrum is attributed to the ZnSe host. Our calculations will potentially motivate further experimental exploration of TM-doped ZnSe. Finally, the methods used here provide a route towards computational high-throughput screening of TM dopants in III–V materials through a combination of the electronic band structure and crystal-field theory.